MORPHOLOGY OF OCCLUSAL SURFACE OF DECIDUOUS MOLARS AFTER ENAMEL ACID ETCHING - N.V. Bidenko (Ukrainian Medical Stomatological Academy, 2015)
Composites and compomers are the dental materials for restoration of permanent and primary teeth and for caries prevention - fissure sealing. They are used with adhesive systems which provides for micromechanical retention and need acid etching of dental tissues before application. However differences between morphology of permanent and deciduous dental tissues determine some morphological peculiarities of result of deciduous enamel etching. There are only few researches devoted to occlusal enamel morphology after acid etching. Objective. To investigate a morphology of etched occlusal enamel of deciduous molars according to localization of etched area and etching duration. Methods. 30 intact extracted because of medical indications deciduous molars were selected. They didn't have any caries and non-carious lesions or other defects of coronal parts. All teeth were washed with distilled water after extraction, their roots were removed 2 mm. below enamel-dentinal junction. Enamel surface was cleaned with toothpaste without fluoride (R.O.C.S. baby, Russia) using rubber cups Pro cup (KerrHawe, U.S.A). All the teeth were immersed into antiseptic solution (chloramine 0,5%) and were stored in a cool place (temperature +4ºC) not longer than 1 month. Then the etching of teeth occlusal surfaces during 20 s (10 teeth), 60 s (10 teeth) or 120 s (10 teeth) with 37,5% phosphoric acid (Н3РО4, Kerr, U.S.A.) was performed. After etching all samples were washed with distilled water during 1 min (for the first and the second groups) and 2 min (for the third group). The final step of examples preparation was their dehydration with ethyl alcohol of ascending concentrations (30º, 70º, 96º). The samples were examined with using of scanning electronic microscope (X-Ray MicroAnalyzer Super Probe 733, Jeol, Japan) after deposition of thin gold layer (Ion Sputter JFC-110, Jeol, Japan and Ion Coater 1B-3, Eico, Japan). Morphology of etched enamel was analyzed for different areas such as cusp top, cusp inner slope and fissure. Etching types were classified according to L.M.Silverstone et al. (1975) and K.A.Galil & G.Z.Wright (1979). Results. The partial removing of enamel aprismatic layer and insufficient enamel prisms exposure on cusp top and cusp slope were observed in examples after 20 s etching with phosphoric acid. The remained aprismatic layer looked like wide coating or small islands on enamel surface, but it was absent on most area of cusp tops. There were II and I types of etched enamel on areas with prismatic structure. Prismatic structure in fissures was completely covered with aprismatic layer and deposits. The morphological picture of occlusal enamel etched during 60 s was different. Aprismatic layer was completely absent on cusp tops and cusp slopes, and etched surface showed II and I (rare) types. However the prismatic structure in fissures was generally covered with aprismatic layer with border parallel to fissure direction. There were no quality etching in majority of fissure areas. The same picture was observed after acid etching of occlusal surfaces during 120 s. Thereby, aprismatic layer remains for a long time in fissure of temporary molars. It doesn't dissolve even after 120 s of acid etching. Prolonged presence of this layer on occlusal surface of deciduous molar may be explained by less chewing load in children and low level of mineralization of antagonists. The question is: if it is possible to obtain a sufficient adhesion of composite sealant in deciduous molars when microretentional structure in this areas after acid etching is absent? In these cases sealant retention may be provided with a good quality of etching of cusp slopes (during 60 and 120 s). That is why fissure sealing with composite sealants may be performed for deciduous molars after acid etching not less than 60 s. Conclusion. The etching of occlusal deciduous enamel with 37 % phosphoric acid provides for retention structure suitable for micromechanical adhesion. The morphology of etched occlusal enamel of temporary molar depends on localization of etched area and etching duration. The high quality of etching of cusp slopes during 60 s and 120 s confirms the possibility of good retention of composite sealants in this areas of temporary teeth.